Polycrystalline indium films in the percolation threshold regime: Time correlation between electric conduction and optical properties with film morphology - Clark, Neville (2014)
Polycrystalline indium films have been deposited at room temperature by electron beam evaporation on amorphous quartz substrates. Once deposited, electrical resistance and specular reflection of the films, for wavelengths between 250 and 920 nm, has been measured in situ. For these as-deposited films, these parameters decrease with time for several minutes until equilibrium is reached. At this state, additional specular and diffuse reflection, and direct transmission measurements were carried out ex situ, as well as atomic force microscope characterizations of the films' surface. The specular reflection spectra are inverted to obtain the intrinsic scattering and absorption coefficients including their time variations. These parameters are successfully correlated with corresponding volumetric scattering and absorption cross sections of submicron- and nano-sized indium particles calculated from Mie theory. The decrease of electrical resistance with time is explained in terms of an increase of the average size of some of the nano-sized grains due to mass transfer from large submicron-sized grains, a manifestation of an inverse Ostwald ripening process. The decrease of specular reflection is related to the decoupling of the surface plasmons oscillating in neighboring nano-sized particles due to the growth of some of them.